2017
DOI: 10.1167/iovs.17-22449
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil and T-Cell Homeostasis in the Closed Eye

Abstract: PurposeThis study sought to examine the changes and phenotype of the tear neutrophil and T-cell populations between early eyelid closure and after a full night of sleep.MethodsFourteen healthy participants were recruited and trained to wash the ocular surface with PBS for at-home self-collection of ocular surface and tear leukocytes following up to 1 hour of sleep and a full night of sleep (average 7 hours), on separate days. Cells were isolated, counted, and incubated with fluorescently labeled antibodies to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 66 publications
1
35
2
Order By: Relevance
“…Postnikoff et al. recently reported that after 7 h of sleep, closed eyes were infiltrated by neutrophils, T cells, and monocytes . The presence of viable neutrophils in tear films was also observed by trypan blue and PI exclusion in another study .…”
Section: Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…Postnikoff et al. recently reported that after 7 h of sleep, closed eyes were infiltrated by neutrophils, T cells, and monocytes . The presence of viable neutrophils in tear films was also observed by trypan blue and PI exclusion in another study .…”
Section: Resultsmentioning
confidence: 68%
“…The neutrophilrelated proteins like MPO, NE, and CG and protein S100 were iden- monocytes. 24 The presence of viable neutrophils in tear films was also observed by trypan blue and PI exclusion in another study. 25 In the evening TF, C5a showed higher values (P < 0.01, Fig.…”
Section: Eye Rheum Is a Form Of Aggnet Agglomerating Particulate Mattmentioning
confidence: 71%
“…In this study, human subjects collected samples of sterile saline rinse applied to the ocular surface upon awakening in the morning. Using saline eye wash to collect microbiome samples is novel and less invasive than swabs of the ocular surface that has previously been used for the collection of tear leukocytes 18,20 . In a series of pooled samples from both eyes, the closed eye tear microbiome in individuals with dry eye disease was distinct from that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence may also suggest the immune system of the closed eye cannot regulate the ocular surface microbiome during sleep. In the closed eye, preliminary evidence suggests higher numbers of neutrophils with an enhanced degranulation response in dry eye disease 18,20 , indicating a dysregulated immune response. This dysregulation may permit increased microbial diversity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, human subjects collected samples of sterile saline rinse applied to the ocular surface upon awakening in the morning. Using saline eye wash to collect microbiome samples is novel and less invasive than swabs of the ocular surface, which has been routinely used for the collection of tear leukocytes 18,20 . In a series of pooled samples from both eyes, the closed eye tear microbiome in individuals with dry eye disease was distinct from that in healthy controls.…”
Section: Discussionmentioning
confidence: 99%